Direct observation of the CVD growth of monolayer MoS2 using in situ optical spectroscopy - López-Posadas, Claudia Beatriz; Wei, Yaxu; Shen, Wanfu; Kahr, Daniel; Hohage, Michael; Sun, Lidong (Beilstein Journal of Nanotechnology, 2019)
Real-time monitoring is essential for understanding and precisely controlling of growth of two-dimensional transition metal dichalcogenide (2D TMDC) materials. However, it is very challenging to carry out such studies during chemical vapor deposition (CVD). Here, we report the first, real time, in situ study of the CVD growth of 2D TMDCs. More specifically, the CVD growth of a molybdenum disulfide (MoS2) monolayer on sapphire substrates has been monitored in situ using differential transmittance spectroscopy (DTS). The growth of the MoS2 monolayer can be precisely followed by observation of the evolution of the characteristic optical features. Consequently, a strong correlation between the growth rate of the MoS2 monolayer and the temperature distribution in the CVD reactor has been revealed. Our results demonstrate the great potential of real time, in situ optical spectroscopy to assist the precisely controlled growth of 2D semiconductor materials.
Keywords: chemical vapor deposition (CVD); in situ differential optical spectroscopy; molybdenum disulfide (MoS2) monolayer; two-dimensional transition-metal dichalcogenides (2D TMDC)